Development of Multi-Disciplinary Teamwork Skills for Engineering Undergraduates - Git, H. M. (2008)
Teamwork skills are expected and demanded of engineers in the job market today, be it in the private or public sector. As evident from job advertisements, employers emphasize the importance of teamwork skills by setting them as an eligibility requirement for the candidates. Technical competence is important, but is not adequate in facing the challenges that await an engineer in the professional practice nowadays. The increasingly diverse and multi-disciplinary nature of the working environment adds to the complexity of team-based operations. The trend towards globalization further prompts for rapid adaptation to the working environment in order to function well and deliver satisfactory performance in the job. Recognizing the need to equip engineering graduates with not only technical know-how, but also the ability to work within a multi-disciplinary team-based setting, Universiti Teknologi PETRONAS (UTP) has introduced and developed a unique course identified as the Engineering Team Project (ETP). ETP aims to provide students with an early exposure to the intricacies and challenges expected in the real working world. The present paper discusses the UTP experience with the ETP curriculum vis-à-vis teamwork skills within a multi-disciplinary context, in response to the dynamic requirements of the stakeholders.